The Influence Of Organizational Culture, Work Ethos And Work Discipline On Employee Performance - Juliati, Fina (AKADEMIK: Jurnal Mahasiswa Ekonomi & Bisnis, 2021)
The purpose of this study was to determine the effect of organizational culture, work ethic and discipline on the employees working performance either partially or simultaneously. The results showed that organizational culture based on partial test was positive and significant effect on the performance, while work ethos can be good too was positive and significant effect on the performance, then work discipline also was positive and significant effect on the performance. The result of correlation coefficient can be summed up the effect of the variable X1 (organizational culture), X2 (work ethos) and X3 (discipline) to variable Y (employees performance) where the relationship is positive. Provisions applicable for F-value greater than F-table (53.874 > 2,80), it can be stated that the multiple correlation is significant. Thus the null hypothesis (H0) that states there is no effect between organizational culture, work ethos and discipline influence on employees performance is rejected, while the alternative hypothesis (Ha) is accepted.